Experimental Study of Dielectric Performance of Insulating Stand-offs under Lightning Impulse - Kurmi, Gyanendra Kumar; Gautam, Basanta Kumar (Journal of Science and Engineering, 2025)
Electrically insulated lightning protection systems (EILPS) utilize insulating standoffs and insulated conductors to maintain the required separation distance from grounded objects. This thesis investigates the dielectric strength of insulating standoffs in electrically insulated lightning protection systems (EILPS) under standard lightning impulse voltages. These stand-offs are crucial for protecting structures, electrical equipment, and personnel from lightning strikes. The study aims to assess their ability to maintain insulation properties during real-world lightning events. The dielectric strength of these standoffs is influenced by factors such as material properties, geometry, environmental conditions, and applied voltage waveforms. By testing the dielectric strength of these standoffs, it is possible to minimize the risk of failure and ensure the system remains functional in the event of a lightning strike. The experiments measured the breakdown voltage, the discharge current, and the flashover time. The results showed a higher 50% flashover voltage (U50) for positive polarity, and an increased (U50) with stand-off length. Negative polarity exhibited higher discharge currents and larger standard deviations in (U50) with length. The time to flashover was higher under positive polarity, with reduced polarity effect at high voltages. The gap conductance increased with voltage, showing lower conductance for positive polarity and higher conductance for shorter standoffs.